Política imperial, presión fiscal y crisis política en el virreinato del Perú durante el gobierno del virrey conde de Castellar, 1674-1678 - Suárez, Margarita (2015)
The aim of this paper is to analyze the measures taken by the viceroy conde de Castellar to clean up the Royal Treasury. As we will show, in the first half of the seventeenth century the treasury was managed by viceroys and royal officials in close collaboration with the financial and commercial sectors which were under the guardianship, or enjoyed the favor, of the representatives of the monarch. When Castellar arrived, in 1674, he tried to correct some of the irregularities that existed in the treasury, and this policy was successful insofar as he succeeded in increasing the income of the Caja of Lima after the destruction of the 1660s. However, he had to confront the royal officials and, above all, the Consulado of Lima, which was responsible for the most important income of the Caja of Lima after remittances from mining. In the blink of an eye, the viceroy changed the terms of the relationship between the commercial elite, the viceroys and the Royal Treasury.